Prediction of superhard carbon allotropes from the segment combination method - He, Ch.; Sun, L.Z.; Zhong, J. (Сверхтвердые материалы, 2012)
Many superhard allotropes of carbon have been proposed in recent years for the purpose of explaining the superhard carbon phases observed in the processes of cold compressing graphite and carbon nanotubes. In this paper, we have reviewed recent advances in searching for superhard phases of carbon from a segment combination view and found that they can be divided into two groups: (i) combinations of segments from cubic diamond and hexagonal diamond with 5-6-7 carbon rings and (ii) combinations of segments from hexagonal diamond and mutated hexagonal diamond with 4-6-8 carbon rings. Finally, an additional example of extending these allotropes of carbon to their corresponding boron nitride counterparts has been discussed. В останні роки було запропоновано безліч надтвердих алотропів вуглецю для пояснення його надтвердих фаз, які спостерігають в процесах холодного стиснення графіту і вуглецевих нанотрубок. У даній статті розглянуто останні досягнення в пошуках надтвердих фаз вуглецю з погляду методу комбінації структурних сегментів і виявлено, що вони можуть бути розділені на дві групи: 1) сполучення сегментів кубічного алмазу і гексагонального алмазу з 5-6-7-членними кільцями вуглецю і 2) сполучення сегментів гексагонального і мутованого гексагонального алмазу з 4-6-8-членними вуглецевими кільцями. Нарешті, розглядається відповідність алотропів вуглецю можливим структурам нітриду бору. В последние годы было предложены много сверхтвердых аллотропов углерода для объяснения его сверхтвердых фаз, наблюдаемых в процессах холодного сжатия графита и углеродных нанотрубок. В данной статье рассмотрены последние достижения в поиске сверхтвердых фаз углерода с точки зрения метода комбинации структурных сегментов и обнаружено, что они могут быть разделены на две группы: 1) сочетания сегментов кубического и гексагонального алмаза с 5-6-7-членными кольцами углерода и 2) сочетания сегментов гексагонального и мутированного гексагонального